Diacerein Loaded Novasome for Transdermal Delivery: Prepartion , In-Vitro Characterization and Factors Affecting Formulation - Albassam, Noor Yousif; Kassab, Hanan Jalal (Iraqi Journal of Pharmaceutical Sciences, 2023)
Diacerein (DCN) is a semi-synthetic anthraquinone derivative of Rhein that is indicated for the management of osteoarthritis. Diacerein exhibits poor dissolution in the GIT fluids and suffers from low bioavailability upon oral administration in addition to the laxative effect of Rhein metabolites. The aim of the present study was to develop novasomal vesicles with optimized entrapment efficiency and size to serve as a carrier for transdermal delivery of diacerein. Novasomal vesicles were prepared by thin film hydration method thin film hydration. The prepared vesicles were optimized utilizing different surfactant to cholesterol molar ration, sonication type, different sonication times and varying fatty acid level. The prepared vesicles were characterized for drug entrapment efficiency, vesicle size and PDI. The best formula was further investigated for zeta potential ten TEM and compatibility study by FTIR analysis. Results showed that F6 was the best formula regarding it vesicle size 275.2± 2.68nm , entrapment efficiency 69.415± 0.234 % and PDI 0.309± 0.016. In conclusion , novasomal dispersion could be successfully formulated with thin film hydration method. Keywords: Diacerein , Novasome , Transdermal Delivery ,Vesicular System .